The Development of E-Atlas Avifauna of Surabaya as an Identification Tool of Birds and to Train Environmental Care Character for X Grade Students - Utami, Ainun Nur Rizka; Ambarwati, Reni (FMIPA UNNES, 2022)
Increasing community participation in efforts to conserve natural resources is one of the important factors in conservation efforts. Therefore, it is necessary to train the character of caring for the environment in the community, one of which is by integrating it into biology learning at school. The purpose of this research was to produce a valid and practical E-Atlas Avifauna Surabaya of Surabaya as Identification Tool of Birds and to Train Environmental Care Character for Grade X Students. This research used a 4D development model without the dissemination stage. The validity of the E-Atlas was measured based on validation from education experts, material experts, and media experts. The practicality of the E-Atlas was measured based on the response of education practitioners (teachers) and students to the E-Atlas, as well as the response of the students’ environmental care character. The data obtained were analyzed descriptive-quantitatively. The results showed that the E-Atlas Avifauna was declared valid or feasible with an overall mode of 4. The E-Atlas Avifauna was declared practical with a teacher’s practical response percentage of 97.7%, a students’ practical response percentage of 95.2%, and a caring character response students’ environment percentage of 80% and 84% with practical categories. Thus, it can be concluded that the E-Atlas Avifauna Surabaya that has been developed is declared valid and practical as an identification tool for birds and to train environmental care characters of X Grade students